Vocational training in Germany - Reuling, Jochen [Mitarbeiter]; Schmidt, Hermann [Mitarbeiter]; Alex, László [Mitarbeiter]; Kath, Folkmar [Mitarbeiter]; Sauter, Edgar [Mitarbeiter]; Schmidt, Jens U. [Mitarbeiter]; Pütz, Helmut [Mitarbeiter] (My University, 2000)
Der vorliegende Band aus der Reihe "Results, Publications and Material from BIBB" vereint Aufsätze und schriftliche Fassungen von Vorträgen zu verschiedenen Aspekten des Berufsbildungssystems in Deutschland. Inhalt: REULING, JOCHEN: Pathways for Youth, S. 5-7; SCHIMDT, HERMANN/ALEX, LASZLO: The Dual System of Vocational Education and Training in Germany, S. 9-19; REULING, JOCHEN: The German "Berufsprinzip" as a Model for Regulating Training Content and Qualification Standards, S. 21-40; KATH, FOLKMAR: Company Training in Germany, S. 41-60; SAUTER, EDGAR: Continuing Vocational Training in Germany, Structures and Developments, S. 61-81; REULING, JOCHEN: Qualifications, Unitisations and Credits - the German Debate, S. 83-91; SCHMIDT, JENS U.: Next Final Examinations for Apprenticeships: Realistic, Action-Oriented, Integrated, Holistic?!, S. 93-104; SAUTER, EDGAR: The Risks and Opportunities of Learning on the Job, S. 105-115; KATH, FOLKMAR: Financing of Vocational Education and Training in the Dual System in Germany. Problems and Possible Solutions, S. 117-130; PÜTZ, HELMUT: New Trends of Development and Models of Reform in the Field of Vocational Education and Training in the Transition to the 21th Century, S. 131-136. (BIBB)
Keywords: S System beruflicher Bildung; S 1.3.1 Ausbildung im Dualen System; I 2.1 Deutschland; Berufsbildungssystem; Duales System; Betriebliche Berufsausbildung; Bundesrepublik Deutschland